2007
DOI: 10.1137/s0895480102414107
|View full text |Cite
|
Sign up to set email alerts
|

Adjacent Vertex Distinguishing Edge‐Colorings

Abstract: An adjacent vertex distinguishing edge-coloring of a simple graph G is a proper edge-coloring of G such that no pair of adjacent vertices meets the same set of colors. The minimum number of colors χ a (G) required to give G an adjacent vertex distinguishing coloring is studied for graphs with no isolated edge. We prove χ a (G) ≤ 5 for such graphs with maximum degree Δ(G) = 3 and prove χ a (G) ≤ Δ(G) + 2 for bipartite graphs. These bounds are tight. For k-chromatic graphs G without isolated edges we prove a wea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
117
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(130 citation statements)
references
References 6 publications
2
117
0
1
Order By: Relevance
“…It is easy to see that ndi(C 5 ) = 5 and in [8] it is conjectured that ndi(G) ≤ (G)+2 for any connected graph G = C 5 on n ≥ 3 vertices. The conjecture has been confirmed by Balister et al [3] for bipartite graphs and for graphs G with (G) = 3. Edwards et al [5] have shown even that ndi(G) ≤ (G) + 1 if G is bipartite, planar, and of maximum degree (G) ≥ 12.…”
mentioning
confidence: 63%
See 2 more Smart Citations
“…It is easy to see that ndi(C 5 ) = 5 and in [8] it is conjectured that ndi(G) ≤ (G)+2 for any connected graph G = C 5 on n ≥ 3 vertices. The conjecture has been confirmed by Balister et al [3] for bipartite graphs and for graphs G with (G) = 3. Edwards et al [5] have shown even that ndi(G) ≤ (G) + 1 if G is bipartite, planar, and of maximum degree (G) ≥ 12.…”
mentioning
confidence: 63%
“…On the other hand, by [3], ndi(G) ≤ 5 for these graphs. Using the concept of maximal (for a given n) Sidon sets, S n (that is any maximal size subset of [n] whose each pair of distinct elements has a unique sum, i.e., a…”
Section: Cubic Hamiltonian Graphsmentioning
confidence: 94%
See 1 more Smart Citation
“…Recently, an adjacent vertex distinguishing edge-coloring [1] of a simple graph G is a proper edge-coloring of G such that no pair of adjacent vertices has the same set of colors. The minimum number of colors of G is the adjacent vertex-distinguishing chromatic number, denoted by…”
mentioning
confidence: 99%
“…In 2006, Baril [2] show that the adjacent vertex-distinguishing chromatic number of the multidimensional mesh and the hypercube both are equal to the maximum degree of the both graphs plus one. In 2007, Balister [1] prove for bipartite graphs or such graphs with maximum degree…”
mentioning
confidence: 99%